Quantifying the impacts of diverse vegetation-covered patterns on hillslope soil erosion: a case experiment of alfalfa-covered hillslopes - Yao, Chong; Zhang, Qingwei; Chen, Kebing; Zhang, Shige; Zhu, Ming; Gu, Zhijia; Yan, Wei; Wu, Faqi (Frontiers in Plant Science, 2025)
IntroductionThe discrepancies in near-soil-surface hydrologic processes triggered by herbage spatial distribution pattern greatly influence the variation in hillslope erosion process. However, knowledge about the influence of herbage spatial distribution pattern on hillslope erosion is still limited.MethodsIn the current study, runoff plots (length × width × depth, 2 × 1 × 0.5 m) with slope gradient of 8.75%–36.40% and a side-spray rainfall simulator with rainfall intensity of 90 mm h-1 were adopted to rainfall simulation. Four herbage spatial distribution patterns with vegetation coverage of 50% (US, upper hillslopes; MS, middle hillslopes; LS, downstream hillslopes; and SS, equally spaced planting) and bare soil (CK) were arranged to quantify the response of hillslope erosion process to alfalfa spatial distribution pattern.ResultsThe results indicated that the initial runoff generation time followed the order of CK, US, MS, LS, and SS. Compared with CK, the mean runoff rate and sediment yield rate for alfalfa-covered hillslopes decreased by 7.18% to 83.77% and 12.62% to 85.69%, and sediment concentration decreased by 0.26 to 2.22 g L-1. The sediment reduction benefits (SRB) and runoff reduction benefits (RRB) followed the order of SS, LS, MS, and US. The average infiltration rates for CK and alfalfa-covered hillslopes with slope gradient of 8.75%–36.40% were 0.17 to 0.50 and 0.28 to 1.35 mm m-2 min-1, respectively.DiscussionAs the results of shielding and protection effect of alfalfa, initial runoff generation time was delayed, infiltration rate was enhanced, and runoff and sediment yield rates were reduced; thus, soil loss was lowered on alfalfa-covered hillslopes. The research provided scientific reference for understanding the anti-erosion of herbage spatial distribution pattern and theoretical guidance for formulating soil and water conservation planning.